Double-blind fluoxetine trial in comorbid MDD–CUD youth and young adults - Cornelius, Jack R.; Bukstein, Oscar G.; Douaihy, Antoine B.; Clark, Duncan B.; Chung, Tammy A.; Daley, Dennis C.; Wood, D. Scott; Brown, Sandra J. (Drug and alcohol dependence, 2010)
This study compared the acute phase (12-week) efficacy of fluoxetine versus placebo for the treatment of the depressive symptoms and the cannabis use of adolescents and young adults with comorbid major depression (MDD) and a cannabis use disorder (CUD) (cannabis dependence or cannabis abuse). We hypothesized that fluoxetine would demonstrate efficacy versus placebo for the treatment of the depressive symptoms and the cannabis use of adolescents and young adults with comorbid MDD/CUD. We conducted the first double-blind placebo-controlled study of fluoxetine in adolescents and young adults with comorbid MDD/CUD. All participants in both treatment groups also received manual-based cognitive behavioral therapy (CBT) and motivation enhancement therapy (MET) during the 12-week course of the study. Fluoxetine was well tolerated in this treatment population. No significant group-by-time interactions were noted for any depression-related or cannabis-use related outcome variable over the 12-week study. Subjects in both the fluoxetine group and the placebo group showed significant within-group improvement in depressive symptoms and in number of DSM diagnostic criteria for a CUD. Large magnitude decreases in depressive symptoms were noted in both treatment groups, and end-of-study levels of depressive symptoms were low in both treatment groups. Fluoxetine did not demonstrate greater efficacy than placebo for treating either the depressive symptoms or the cannabis-related symptoms of our study sample of comorbid adolescents and young adults. The lack of a significant between-group difference in these symptoms may reflect limited medication efficacy, or may result from efficacy of the CBT/MET psychotherapy or from limited sample size.